(untitled) (Research, Society and Development, 2020)
Microbiology is the branch of Biology that studies bacteria, fungi, protozoa, unicellular algae, viruses, viroids and prions. The teaching of Microbiology in Basic Education has proved to be quite challenging, not only for the teacher, who often does not have adequate materials for his classes, but also for students who are learning about such an abstract subject, which are microorganisms. Basic knowledge of microbiology is very important since it is directly associated with health, personal hygiene and the maintenance of the environment. It is known that the majority of science classes taught in Basic Education are traditional, and often do not allow for meaningful learning. It is necessary to think of teaching-learning strategies that are efficient in this process, such as the use of experiments. Therefore, this study aimed to analyze 10 Science books of the 7th year of PNLD 2017, especially the chapter that contemplates microorganisms. This analysis is based on the presence of experiments, exercises, cohesive images and how each group of microorganisms is approached in contextualizing the contents. With the result of the analysis of the books, it can be seen that there is a deficiency in the presence of experiments, and that only the book as a didactic tool is not enough for meaningful learning.